Improved access to finance : a key to SME growth - Rosen, Harold (2003)
Looks at project development facilities and SME facilities around the world. Concludes that no effort toward reduction in developing nations is sustainable without growth of SMEs. Suggests that one of the first steps toward a vibrant SME sector is the opening of more financing channels, and ensuring that they are focused on building strong partnerships and trust between SMEs and their local banks.